The Mediating Role of Financial Performance on The Influence of Corporate Social Responsibility and Good Corporate Governance on Firm Value - Rusmawati, Zeni; Mauliddah, Nurullaili; Sari , Tyasha Ayu Melynda (Universitas Muhammadiyah Sorong, 2025)
This research aims to determine the influence of Corporate Social Responsibility and Good Corporate Governance on firm value with financial performance as a mediating variable. The research used quantitative research using panel data and multiple regression analysis with SPSS 27. This research uses a purposive sampling technique with the object being raw materials sector companies listed on the Indonesia Stock Exchange (BEI) in 2018-2023. The number of observation samples is 90. The results of this research indicate that financial performance cannot mediate the influence of CSR on company value, but financial performance can mediate the influence of GCG on firm value. This implies that investors will pay attention to the company's financial performance, when looking at corporate governance (GCG).